Interpolated scales of approximation spaces for regular elliptic operators on compact manifolds - Dmytryshyn, M.I. (Carpathian Mathematical Publications, 2014)
We define the interpolated scales of approximation spaces, generated by regular elliptic operators on compact manifolds. The appropriate Bernstein-Jackson inequalities and application to spectral approximations of regular elliptic operators are considered.